Da’wa in Islam: A Discursive Analysis of South Asian Muslim Scholarly Discourses - Owais Manzoor Dar (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
Da‘wa is one of the notable/substantial topic in Islam. Numerous works have been written on the subject, its modus operandi, philosophies, pedagogy, prominence, tactics, and other interconnected aspects in distinctive languages especially Arabic, Urdu and English. In South Asia, the enormous da‘wa literature produced by the scholars is in Urdu. A significant portion of literature, however, has been produced, both originally as well as through translations, in English to fulfill the needs of da‘uāt in South-Asia as well as global level. In this context, the study attempts to present an appraisal of three English works (produced in 1990s to 2000s) authored by the South Asian scholars. These books are: Syed Abul Hasan Nadwi, da‘wa in the West: The Qur’anic Paradigm (1992 [1991]); Abdus Salam, da‘wa Guide (1996); and Amin Ahsan Islahi, Da’wat-ī dīn Aur Uska Tāriqa-Ka’ar/Islamic Faith and the Mode of its Preaching (2005[1951]). The main themes, collectively, highlighted in these works, reveal both theoretical, and practical aspects; pedagogy and methodology of da‘wa in Quranic paradigm; practical aspect from Prophet’s life; modes and stages in dawat-ī dīn; qualities; language; principles and the style of articulation; wisdom and broadness of da‘i; da‘wa and its harmony with time and space (Modern age). The study, with a tri-fold aim, seeks to: (i) explore their approaches and methodology in their discussions on da‘wa (ii) evaluate critically their stance on modern-day challenges of da‘wa and (iii) highlight the relevance of their interpretation in providing solutions to the contemporary challenges vis-à-vis da‘wa . The major argument put forth in the article is that these selected books make a significant contribution in understanding the pros and cons of da‘wa through their contents; approach and style; construct a momentous contribution to da‘wa literature in the English language and thus accomplish the need of da‘uāt glocally.